Gas–Liquid–Solid Triphase Interfacial Chemical Reactions Associated with Gas Wettability. Issue 6 (25th January 2021) - Li, Zhaohua; Hu, Rui; Song, Jun; Liu, Liwei; Qu, Junle; Song, Weiguo; Cao, Changyan
Abstract: Wettability is widely studied in biological systems and attracts tremendous attention in numerous fields. Gas wettability has been increasingly investigated for the past few years because of the presence of gases in many reactions that are essential to environmental protection, health monitoring, energy conversion, and industrial catalysis. In general, traditional liquid–solid diphase systems with poor solubility and tardy diffusion of gases severely hinder the reaction efficiency. Researches show that this problem can be effectively solved by creating a gas–liquid–solid triphase reaction system through the regulation of gas wettability. This study summarizes the latest advances in creating appropriate gas wettability to introduce gas–liquid–solid triphase interfaces in gas‐involved reactions for enhanced catalytic performance. In these triphase systems, gaseous reactants are transported directly from the gas phase to active sites while gaseous products are rapidly removed from the catalyst surface, realizing efficient mass transport and consequently improving the reaction activity and selectivity. Reactions summarized are gas‐consuming reactions and gas‐forming reactions, which are further divided into photocatalytic reactions, bioelectronic reactions, electrochemical reactions, and heterogeneous thermocatalytic reactions. For the first time, heterogeneous thermocatalytic reactions are included in the system, thus forming a relatively comprehensive review of this field so far. Abstract : Gas–liquid–solid triphase interfacial chemical reactions associated with gas wettability are summarized, including gas‐consuming reactions and gas‐forming reactions. These two types of reactions are further described in detail from the aspects of photocatalytic reactions, bioelectronic reactions, electrochemical reactions, and heterogeneous thermocatalytic reactions. For the first time, heterogeneous thermocatalytic reactions are included in the system.